2013
DOI: 10.1016/j.eplepsyres.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the source of cerebellar epilepsy: Hemifacial seizures associated with cerebellar cortical dysplasia

Abstract: Summary Traditionally, subcortical structures such as the cerebellum are supposed to exert a modulatory effect on epileptic seizures, rather than being the primary seizure generator. We report a 14-month old girl presenting, since birth, with seizures symptomatic of a right cerebellar dysplasia, manifested as paroxystic contralateral hemifacial spasm and ipsilateral facial weakness. Multimodal imaging was used to investigate both anatomical landmarks related to the cerebellar lesion and mechanisms underlying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…lissencephaly 2 and Walker‐Warburg syndrome; ARX phenotypes). Rare cases of cerebellar dysgenesis in patients with epilepsy have been described, however (Lascano et al ., ). The infrequent cerebellar ganglioglioma merits further consideration, but present evidence does not refute the concept that the cerebellum is synaptically stable with low epileptogenic potential.…”
Section: Synapatic Factors Conducive To Epileptogenesismentioning
confidence: 99%
“…lissencephaly 2 and Walker‐Warburg syndrome; ARX phenotypes). Rare cases of cerebellar dysgenesis in patients with epilepsy have been described, however (Lascano et al ., ). The infrequent cerebellar ganglioglioma merits further consideration, but present evidence does not refute the concept that the cerebellum is synaptically stable with low epileptogenic potential.…”
Section: Synapatic Factors Conducive To Epileptogenesismentioning
confidence: 99%
“…the finger-nose-finger test). The issue is not exclusive to MEG -to date, few studies with scalp cerebellar EEG have been reported (Muthukumaraswamy et al 2003;Lascano et al 2013;Todd et al 2018). It is widely assumed that scalp EEG recordings for the cerebellum suffer from muscle artefacts (Muthukumaraswamy, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gangliogliomas are among the most common epileptogenic lesions in epilepsy centers [21], harboring a major propensity for spontaneous electrical discharges which probably explains the association of this lesion to this unique syndrome [22]. Not unexpectedly, histological studies of cerebellar or fourth ventricle lesions presenting with subcortical epilepsy were classified as ganglioglioma [2,4,9,10,12,[23][24][25][26][27], hamartoma [8,13,14,28], gangliomatous hamartoma [29], ganglioneurocytoma [30][31][32] or low-grade dense fibrillary astrocytoma [3,15]. Although many of these lesions may carry a developmental origin and actually represent a continuum with FCD, some are not intrinsically epileptogenic [33].…”
Section: Discussionmentioning
confidence: 95%